Digital surveillance: The interests in toothache‐related information after the outbreak of COVID‐19. (2nd September 2021) - Rizzato, Veridiana Lopes; Lotto, Matheus; Lourenço Neto, Natalino; Oliveira, Thais Marchini; Cruvinel, Thiago
Abstract: Objectives: The aim of this ecological study was to analyze the relationship of social restriction measures and people's interest in searching toothache‐related information on the Internet. Materials and Methods: The following indicators Stringency Index (SI), Years Lived with Disability (YLDs) for untreated caries in permanent teeth, Google market share, Internet penetration, and relative search volume (RSV) for the Topic "Toothache" in Google Trends were determined for 21 countries with available data, from April 2018 to May 2020. Statistical analysis was performed using Mann–Whitney U test, t ‐Student test, Pearson's Chi‐square test, and Spearman and Pearson's cross‐correlation tests (α = 0.05). Results: Relative search volume values increased significantly after restriction measures in all countries, except for Japan. Higher RSV values were found among 11 countries that presented a cross‐correlation between RSV and SI with r≥│0.6│. The most common queries were linked to the treatment and self‐resolution of toothache, with a sudden increase of searches that combined the symptom with COVID‐19. Conclusions: The interests in toothache‐related digital information were associated with social restriction measures. These results allow the identification of dental demands of distinct populations, contributing to the planning of specific public health policies during and after the pandemic period.